DAMPAK POSITIF DAN NEGATIF PADA TRADISI PERAHU BEGANDUNG DI DESA SEBERANG PANTAU KECAMATAN KUANTAN MUDIK KABUPATEN KUANSING - Yuhelmi, Yuhelmi; Juswandi, Juswandi (Jurnal Ilmu Budaya, 2013)
This writing deals with a ritual called "Perahu Begandung". It highlights the impacts of the tradition in the village in the opposite coast of Kuantan district Mudik Singingi, Kuantan Regency. Positively, this tradition (ritual) makes the people in Kuantan Mudik applies their Islamic doctrine. Socially, this ritual strengthens the spirit of "gotong royong" and economically it increases the local people's income, and the various and colorful ornaments in the boat show the people's artistic taste. Besides, it also affects the people negatively. The coming of the oustider with their inappropriate behavior affects the local people morally. Moreover, the people come, the more crimes occur.